Does rising income inequality affect mortality rates in advanced economies? - Mayvis Rebeira; Paul V. Grootendorst; Peter C. Coyte; Victor Aguirregabiria (Kiel Institute for the World Economy (IfW), 2017)
What effect does rising income inequality have on mortality rates in developed countries? In particular, does the rise of the super-wealthy or the top 0.01% of the population effect overall health of the population? This paper focuses on the effect of rising income inequality on mortality rates of men and women in a subset of OECD countries over six decades from 1950-2008. The authors used adult mortality as the outcome measure and the inverted Pareto-Lorenz coefficient as the preferred measure of income inequality and obtained the latest and precise data on the income inequality measure. They used a panel co-integration econometric framework to address some of the challenges posed by more conventional methods. The findings show that for industrialized countries with co-integrated series, income inequality appears to have a long-run significant negative effect on mortality risk for both men and women, that is, an increase in income inequality does not appear to lower annualized adult mortality rates.
Keywords: I1; C1; 330; income inequality; mortality; health; panel co-integration